2016
DOI: 10.17116/otorino201681270-73
|View full text |Cite
|
Sign up to set email alerts
|

Polypous rhinosinusitis in the children

Abstract: We present an overview of the modern literature concerningpolypous rhinosinusitis (PRS) in the children. The information thus derived is compared with the available results of the clinical investigations involving the adults patients with this pathology. Allergic diseases and mucoviscidosis appear to be the pathological conditions most likely leading to the development of polyps in the nasal cavity. The patients suffering from rhinosinusitis associated with the disorders of arachidonic acid metabolismare very … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
0
1
Order By: Relevance
“…Some authors point that hypertrophic and hyperplastic changes in the sinonasal mucosa are observed mainly in people over the age of 40 [ 12 ]. However, our studies and reports by others indicate that the debut of hypertrophy and hyperplasia can also occur in childhood, although there is no verified data on the prevalence of this pathology in children [ 3 , 13 , 14 ]. According to Karpova et al [ 14 ], in children, polyposis-associated changes in the mucosa of the nose and paranasal sinuses are mainly due to AR.…”
Section: Introductioncontrasting
confidence: 61%
“…Some authors point that hypertrophic and hyperplastic changes in the sinonasal mucosa are observed mainly in people over the age of 40 [ 12 ]. However, our studies and reports by others indicate that the debut of hypertrophy and hyperplasia can also occur in childhood, although there is no verified data on the prevalence of this pathology in children [ 3 , 13 , 14 ]. According to Karpova et al [ 14 ], in children, polyposis-associated changes in the mucosa of the nose and paranasal sinuses are mainly due to AR.…”
Section: Introductioncontrasting
confidence: 61%